2018
DOI: 10.1080/07399332.2017.1411914
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' willingness to pay for daughters' HPV vaccine in northern Vietnam

Abstract: HPV vaccine is effective in preventing human papillomavirus, the main cause of cervical cancer. In Vietnam, at first, it was subsidized at $5 a dose and reached the coverage of 96% in two pilot provinces, indicating potentially high acceptance. Currently, it is provided at $120-195 for three doses. This is a cross-sectional study, conducted in two northern rural districts of Vietnam. Researchers present findings to show 53.1% of mothers stated their willingness to pay (WTP) for HPV vaccine for their daughters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The sample size for the first objective was calculated using a single population proportion formula assuming 95% confidence interval (CI), 5% marginal error (d), and 50% expected acceptance, which yielded the sample size of 384. The sample size for the second objective was determined by using a double population proportion formula using Epi-Info TM 7 software using the following assumptions: 95% CI, power of 80%, Exposed unexposed ratio= 1, and Crude Odds Ratio (COR) of two significantly associated variables ie those parents who always used condoms (OR=1.77) and who perceived vaccination as acceptable (OR=7.91) from a cross-sectional study conducted at North Vietnam, 14 which yields a sample size of 430. Accordingly, the largest sample was obtained from the second objective, and adding a 10% non-response rate and multiplied by a design effect of 2, the final sample size for this particular study was 946.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…The sample size for the first objective was calculated using a single population proportion formula assuming 95% confidence interval (CI), 5% marginal error (d), and 50% expected acceptance, which yielded the sample size of 384. The sample size for the second objective was determined by using a double population proportion formula using Epi-Info TM 7 software using the following assumptions: 95% CI, power of 80%, Exposed unexposed ratio= 1, and Crude Odds Ratio (COR) of two significantly associated variables ie those parents who always used condoms (OR=1.77) and who perceived vaccination as acceptable (OR=7.91) from a cross-sectional study conducted at North Vietnam, 14 which yields a sample size of 430. Accordingly, the largest sample was obtained from the second objective, and adding a 10% non-response rate and multiplied by a design effect of 2, the final sample size for this particular study was 946.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…This could serve as an instrument of health advantages. 21 , 22 , 23 Although academic WTP surveys have been conducted to assess the relative values of various vaccinations, they have rarely been used for booster doses of COVID-19. We believe that a WTP questionnaire would assist in evaluating the most acceptable price of booster doses for the general population at risk of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review of studies on WTP for dengue vaccine revealed that knowledge of dengue vaccine had not been a factor under study previously. However, studies on WTP of other vaccines such as the HPV vaccine, the Ebola vaccine and the Influenza vaccine have assessed the association between knowledge of related vaccines with WTP for those vaccines respectively (Dinh Thu et al, 2018;Kruiroongroj, Chaikledkaew, & Thavorncharoensap, 2014;Mari Kannan Maharajan, Kingston Rajiah, Kelly Sze Fang Num, 2015;Ughasoro, Esangbedo, Tagbo, & Mejeha, 2015;Umeh, Nduka, & Ekwunife, 2016;Worasathit et al, 2015). In three of the aforementioned studies, two on WTP for HPV vaccines and one of WTP for Ebola vaccines, it was shown that knowledge regarding the vaccines had a significant association with WTP for the respective vaccines (Dinh Thu et al, 2018;Mari Kannan Maharajan, Kingston Rajiah, Kelly Sze Fang Num, 2015;Ughasoro et al, 2015).…”
Section: Ijphcsmentioning
confidence: 99%